ApmA Is a Unique Aminoglycoside Antibiotic Acetyltransferase That Inactivates Apramycin - Emily Bordeleau (American Society for Microbiology, 2021)
Apramycin is an aminoglycoside antibiotic that has been traditionally used in veterinary medicine. Recently, it has become an attractive candidate to repurpose in the fight against multidrug-resistant pathogens prioritized by the World Health Organization.